Acute myocarditis in bodybuilder from coxsackievirus and thyrotoxicosis. Issue 4 (October 2016) - Kwak, Tommy; Al Zoubi, Moamen; Bhavith, Aruni; Rueda Rios, Carlos; Kumar, Surender
Abstract: A 25-year-old male with no past medical history presented with 1 day of chest pain. The patient had exercised with high intensity for a bodybuilding competition. He had fever, malaise, sore throat, and cough 1 week before presentation. He was tachycardic and tachypneic. Cardiac examination was unremarkable. Electrocardiogram showed diffuse ST segment elevation. Laboratory results showed leukocytosis, creatinine kinase 3078 unit/L, and troponin I 78.06 ng/mL. Coronary angiography revealed no occlusion. Echocardiogram showed ejection fraction of 45% with global hypokinesis. The next day, the patient became dyspneic, hypoxic, and hypotensive. Chest X-ray showed pulmonary edema requiring intubation for respiratory failure. Inotropic support and intra-aortic balloon pump were started. A viral panel was ordered and antibody titer of coxsackievirus B type 4 was ≥1:640. On obtaining further history, it was found that he took liothyronine 75 mcg daily for 3 weeks. Thyroid-stimulating hormone was 0.015 U/mL and free T3 was 4.4 ng/mL. Burch–Wartofsky score was 75. Methimazole and hydrocortisone were started. Cardiac magnetic resonance imaging showed diffuse myocardial inflammation and edema. There was multifocal dense epicardial and midmyocardial necrosis in all segments. The patient was discharged on metoprolol and enalapril. The patient was instructed to refrain from supplements. <Learning objective: Exogenous thyroid hormone abuse may be an unusual cause of acute myocarditis in young healthy individuals. Physicians should emphasize to athletes to avoid overtraining and to minimize exposure to infection. Athletes with a clinical diagnosis of viral myocarditis should be temporarily excluded from competitive physical activity. Physicians should check whether athletes' immunizations are up-to-date and advise athletes against the use of thyroid hormone.>